Constraints on Inner Core Anisotropy Using Array Observations of P′P′. Issue 21 (4th November 2017) - Frost, Daniel A.; Romanowicz, Barbara
Abstract: Recent studies of PKPdf travel times suggest strong anisotropy (4% or more) in the quasi‐western inner core hemisphere. However, the availability of paths sampling at low angles to the Earth's rotation axis (the fast axis) is limited. To augment this sampling, we collected a travel time data set for the phase P′P′df (PKPPKPdf), for which at least one inner core leg is quasi‐polar, at two high latitude seismic arrays. We find that the inferred anisotropy is weak (on the order of 0.5 to 1.5%), confirming previous results based on a much smaller P′P′ data set. While previous models of inner core anisotropy required very strong alignment of anisotropic iron grains, our results are more easily explained by current dynamic models of inner core growth. We observe large travel time anomalies when one leg of P′P′df is along the South Sandwich to Alaska path, consistent with PKPdf observations, and warranting further investigation. Key Points: Detect inner core phase P′P′df (PKPP KPdf) at two high latitude seismic arrays Infer weak inner core anisotropy of 0.5–1.5% aligned with the rotation axis Observe stronger velocity anomalies with greater variability in magnitude in paths reflecting under the South Sandwich Islands